Behaviour of Axial Bearing Pile under Liquefaction Condition Based on Empirical and 3D Numerical Simulation - Zakariya, Ali; Rifa’i, Ahmad; Ismanti, Sito (Universitas Negeri Semarang, 2023)
The liquefaction phenomenon affects to bearing capacity losses of building foundations. When liquefaction occurs in loose sandy soils, the pore water pressure increases, and the effective soil stress decreases significantly. This study deals with the bored pile foundation of Kretek 2 bridge, which is located in an area with high vulnerability to liquefaction. The study aimed to estimate the axial load-bearing capacity of the foundation of Kretek 2 bridge under liquefaction conditions. This study compares the results of calculations using empirical approaches with 3D numerical simulation modeling using MIDAS GTS NX. The results of the empirical calculations show a reduction in the axial bearing capacity of the foundation under liquefaction conditions of 2.88-8.16% and 2.63-7.23% for the approach of Reese and Wright 1977 and O’Neill and Reese 1989, respectively. While using 3D numerical modeling, although there was a decrease in skin resistance, there was no significant decrease in the total bearing capacity, and it was still above the design load (3632.563456.02 kN). Based on these results, the bearing capacity of the installed Kretek 2 Bridge foundation is still capable of receiving loads during static and liquefaction states.